More About DIPS. - Integrating Distance Per Stroke technique drills and concepts into training, utilising on-going assessment and testing, and introducing distance improvement per stroke into competition - Dodson, A. (coachesinfo.com)
Content: - Introduction - Integrating Distance Per Stroke Technique, Drills, and Concepts into Training Sessions - Use of Ongoing Assessment and Periodic Formal Testing - Examples of Collected Data, Suggested Graphs, and Comments to Swimmers - Examples and Suggested Graphs and Comments to Swimmers - Utilisation of Distance Improvement Per Stroke in Competition - Concluding Points